MERGER, AKUISISI, DAN RESTRUKTURISASI - Ruslim, Herman (Manajemen Bisnis Kompetensi, 2008)
Merger and acquisition have been the major considerations in todays business policy. Merger and acquition will likely take effect if two or more mergering organizations sinergizing their financial and operational strategies. This literature study examines the likelihood of merger and acquition, in terms of restructurization, using risk management framework and stock evaluation framework.Keywords: merger, acquisition, restructurization, risk management, stock evaluation.